Holistic education: the social reality of engineering - TRBUŠIĆ, HELENA (Journal of Education Culture and Society, 2020)
Over the last few decades, scientists exploring the aspects of engineering education and investigating the strong connection between the engineering profession and society have argued for a more rounded, holistic approach to the engineering curriculum. In addition to fundamental technical subjects, they have proposed the inclusion of a broad range of social subjects in order to equip young engineers with social and communication skills relevant for teamwork, and to enhance their awareness about both the way social changes influence the implementation of certain engineering solutions and about the way develop-ments in engineering have a considerable impact on society in general. This paper presents the results of a two-year qualitative study of the importance of social subjects within the engineering academic curriculum at the Faculty of Mechanical Engineering and Naval Ar-chitecture in Zagreb, Croatia.